“We can tell a good teacher who cares, understands, and can be confidential about it”: youth and caregiver experiences with HIV disclosure to schools in Kenya - Moraa, Hellen; Njuguna, Irene; Mugo, Cyrus; Mbwayo, Anne; Nyapara, Florence; Aballa, Calvins; Wagner, Anjuli Dawn; Wamalwa, Dalton; John-Stewart, Grace; Inwani, Irene; O'Malley, Gabrielle (Frontiers in Public Health, 2023)
Introduction Disclosure of one's HIV status to others is often difficult due to the fear of stigma. However, disclosure may facilitate receiving social support. Many youth living with HIV (YLH) are enrolled in school as better treatments have improved the health and survival of children with HIV. There is no structured process for disclosure at school for YLH and their caregivers. We sought to understand school disclosure experiences among YLH and their caregivers and assess the need for the development of a structured disclosure intervention tailored to school settings. Methods We conducted in-depth qualitative interviews with 28 school-going YLH aged 14–19 years and 24 caregivers of YLH. Interviews were conducted in English and Swahili, transcribed, and translated. The transcripts were uploaded to Atlas.ti 9 for thematic analysis. Results YLH and caregivers clearly articulated the benefits of disclosing to school staff. Disclosure to school staff was seen as the first step to receiving support for medication storage, adherence, and clinic attendance. However, disclosure was also perceived to be a very complicated and stressful process. Fear of stigma drove caregivers and YLH toward careful planning of when and to whom to disclose. Distrust of school staff was a significant barrier to disclosure, even among those who clearly articulated the benefits of disclosure. Disclosure to school staff largely resulted in positive experiences; the immediate reactions were positive or somewhat neutral and confidentiality was upheld. The anticipated benefits of practical and emotional support were demonstrated by the school staff to whom the HIV information was disclosed. Conclusion Disclosure of HIV status to someone at school is necessary to receive support for medication adherence. Stigma and the lack of structured support for the disclosure process at school often hinder YLH and their caregivers from disclosing. YLH would benefit from better support at schools, including policies to facilitate disclosure that address the caregiver and YLH's fear of stigma and loss of confidentiality. School policies could also provide guidance on whom to disclose to and available post-disclosure support.